White on White Angst: Exploring White Anxiety When Anticipating Discussing Racial Discrimination - Milton, Mi'Lexus. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Psychology.; Advisor: Keith Maddox.; Committee: Sapna Cheryan, and Samuel Sommers.; Keywords: Social psychology, and Psychology.